Merupa Wujud Evangelikalisme di Indonesia: Suatu Usulan Awal - Yosia, Adrianus (Veritas : Jurnal Teologi dan Pelayanan, 2020)
Shaping the Form of Evangelicalism in Indonesia: A Preliminary Proposal. This article was written as a preliminary opinion to explore the "public face" of evangelicalism as a movement in Indonesia. Furthermore, this article will discuss who are the evangelicals in Indonesia, the theological characteristics of the evangelicals, and the form of evangelical's participation in Indonesia. The writer will argue that the modification from Bebbington's Quadrilateral, Larsen's Pentagram, can be theological characteristics from the evangelicals in Indonesia. As a consequence, this article will propose two ways of movements from evangelicalism in Indonesia, which are the inward and outward movements. The inward movement is the spirit of the evangelical church to reform itself, while the outward flow is the eagerness of the evangelical church to reform the social condition. Thus, these are initial observations for shaping evangelicalism in Indonesia.